Analysis of Law Enforcement Against Illegal Fishing in Central Bangka (Case Study of Misuse of Fishing Gear with Explosives, Trawling, and Poisoning) - Andrieo Vindhya Praguslinardo; Muhamad Adystia Sunggara (Journal of Law, Politic and Humanities, 2024)
This study aims to analyze law enforcement against illegal fishing crimes in Central Bangka, focusing on the misuse of fishing methods using explosives, trawls, and poison. Illegal fishing is a serious problem threatening the preservation of marine resources and the sustainability of fisheries ecosystems. This research is a normative juridical legal research method. The findings reveal that law enforcement against illegal fishing in Central Bangka faces several challenges, such as limited resources for law enforcement officers, low public legal awareness, and weak coordination among relevant agencies. Although regulations on illegal fishing exist, their implementation in the field remains suboptimal. This study recommends enhancing the capacity of law enforcement officers, increasing public legal awareness, and strengthening inter-agency coordination. A holistic approach involving community participation is also necessary for marine resource conservation.